2014
DOI: 10.1016/j.socscimed.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The use of citizens' juries in health policy decision-making: A systematic review

Abstract: Deliberative inclusive approaches, such as citizen juries, have been used to engage citizens on a range of issues in health care and public health. Researchers engaging with the public to inform policy and practice have adapted the citizen jury method in a variety of ways. The nature and impact of these adaptations has not been evaluated. We systematically searched Medline (PubMED), CINAHL and Scopus databases to identify deliberative inclusive methods, particularly citizens' juries and their adaptations, depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
215
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(241 citation statements)
references
References 43 publications
2
215
0
14
Order By: Relevance
“…Our findings confirm that public participation in deliberative forums is common in public health and health policy research and that Community or citizens' juries are the favored deliberative technique (Street et al, 2014). It is also clear that decision makers are seeking input from multiple publics on issues other than health priority setting.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Our findings confirm that public participation in deliberative forums is common in public health and health policy research and that Community or citizens' juries are the favored deliberative technique (Street et al, 2014). It is also clear that decision makers are seeking input from multiple publics on issues other than health priority setting.…”
Section: Discussionsupporting
confidence: 79%
“…It seems public health and health policy researchers may be attuned to this potential and constitute mixed publics in order to compare and combine different perspectives in deliberation. This adds to previous work by researchers including Street et al (2014) and Burgess (2014), who have observed that deliberative processes are more likely to influence public policy when decision-makers are directly involved as research collaborators. However, consistent with much of the critical literature on public engagement exercises, very few of these studies suggested how the information generated might be acted upon, or integrated into policy discussions.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations